Mode of Action of Lomofungin - Gottlieb, David (1969)
Lomofungin inhibited the growth of some yeasts and mycelial fungi at concentrations between 5 and 10 μg/ml. At such concentrations, there was no decrease in endogenous and exogenous oxygen consumption, and even 50 μg of antibiotic per ml caused only slight decreases. The permeation of the cell membrane was changed so that leakage of ninhydrin-positive substances was reduced, and the uptake of (14)C-labeled glucose, amino acids, uracil, and thymidine was decreased at concentrations as low as 4 μg/ml. Protein synthesis in whole cells of Saccharomyces cerevisiae was reduced 35% at 10 μg/ml. However, the antibiotic did not reduce the incorporation of phenylalanine-U-(14)C into polypeptides with cell-free systems of Rhizoctonia solani and S. cerevisiae. The synthesis of ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) was inhibited even at concentrations of lomofungin of 4 μg/ml. Since RNA synthesis was inhibited at lower concentrations and earlier than DNA synthesis, the primary site of action of the antibiotic appears to be the synthesis of RNA.